Factors Affecting Roan and Sable Antelope Populations on Nature Reserves in Transvaal with particular reference to ecophysiological aspects - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 1975.